A randomised, single‐blind technical study comparing the ultrasonic visibility of smooth‐surfaced and textured needles in a soft embalmed cadaver model. (5th November 2014) - Munirama, S.; Joy, J.; Columb, M.; Habershaw, R.; Eisma, R.; Corner, G.; Cochran, S.; McLeod, G.
Summary Visibility of the needle tip and shaft is important during ultrasound‐guided regional anaesthesia in order to prevent nerve trauma. Tip and shaft visibility is reduced when needles are inserted in‐plane at wide angles and out‐of‐plane at narrow angles to the ultrasound probe. Although textured needles are more reflective than smooth needles, we hypothesised that poor visibility of the tip and shaft still remained using the above angle‐probe combinations. In a single‐blind study, we compared the visibility of a textured Tuohy needle, a textured single‐shot needle and a conventional smooth‐surfaced Tuohy needle when inserted into the biceps and deltoid muscles of a soft embalmed cadaver. One hundred and forty‐four needles were block‐randomised to in‐plane and out‐of‐plane insertions at 30°, 45°, 60° and 75° to the ultrasound beam. Two blinded raters assessed needle tip visibility on video recordings of the insertions using a binary scale (0 = not visible, 1 = visible) and shaft visibility using a 5‐point Likert scale. The median (IQR [range]) proportions of visible needle tips were 83% (67–83 [50–100]%) for the textured Tuohy, 75% (67–83 [33–83]%) for the textured single‐shot needle and 33% (33–46 [0–50]%) for the smooth‐surfaced Tuohy (p = 0.0007). Median (IQR [range]) needle shaft visibility was rated as 4.0 (3.5–4.7 [3.0–4.9]) for the textured Tuohy, 4.0 (3.8–4.5 [2.7–4.9]) for the textured single‐shot needle and 3.0 (2.4–3.3 [2.3–3.5]) for the smooth‐surfaced Tuohy (p = 0.015). Nevertheless, visibility was reduced at wide angles in‐plane and narrow angles out‐of‐plane both for needle tips (p = 0.004) and shafts (p = 0.005).